EPIDEMIOLOGICAL AND HISTOPATHOLOGICALSTUDY OF PARAMPHISTOMUM CERVI IN CATTLE INBABYLON PROVINCE - Al-Biaty, Huda; Kadem, Faozya; Al- Naimi, Rajiha; Al –Taae, Eman (Iraqi Journal of Science, 2024)
The aim of this study was to estimate the rate of infection with Paramphistomumin the digestive tract of cows. A total of 268 slaughter cows were examined in Al-Hilla Abattoir from 1 March to the end of November 2009. The rate of infection was3.73% and the highest rate of infection was at summer months (6.45%) while lowerinfection rate was shown at Autumn (1. 2%).Rate of infection in calves at age less than 2 years reached 3.44% and in cows at agebetween 2-4 years reached 4.23 %. Lower percentage at age more than 4 years wasreported (3.17%) Males cows recorded rate of infection with Paramphistomum 4.76% and in females cows reached 2.47%, while the infection rate in hybrid cowswas more than the local cows (4.87% and 2.75% respectively).Pathological changes at necropsy finding showed slight changes with high numbersof parasites in the lumen of rumen attached to the mucosa of rumen at thekeratinized layer. In addition, changes were noted at microscopical examination,which were characterized by infiltration of mononuclear cells in lamina propria forthe mucosa and there was dilation of blood vessels. No changes observed induodenum and jejunum with no presence for immature parasite which gave anindication that most of the infection was with the mature stage.